MOTIVASI KERJA PEGAWAI DI KANTOR BIRO AKADEMIK KEMAHASISWAAN DAN PERENCANAAN (BAKP) UNIVERSITAS TADULAKO - Royfandi, Moh. (Katalogis, 2016)
AbstracThe objective of the research is to know how the employees’ work motivation at Bureau of Academics Students Affairs and Planning (BAKP) Tadulako University. The writer applies descriptive qualitative research method and needs hirarki theory (Abraham Maslow), namely: (1) basic human needs, (2) safety needs, (3) social needs, (4) reward needs, and (5) self actualization needs.The informants of the research are employees’ at Bureau of Academics Students Affairs and Planning (BAKP) Tadulako University. The data of the research are primary data. The technique of data collection are interview, observation, and documentation. Then, the data are analyzed through data reduction, data presentation, and conclusions. From the results of the research, the writer concludes that employees’ basic needs at Bureau of Academics Students Affairs and Planning (BAKP) Tadulako University is fulfilled. But, in safety needs, social needs, reward needs, self actualization is not fulfilled yet. Because all these indicators is not running well as expected and it caused low on employees’ work motivation in working.